Rapid measurement of thoracolumbar kyphosis with the integrated inclinometer of a smartphone: a validity and reliability study - Huang, Tianji; Zhao, Zenghui; Wang, Lin; Zhang, Chao; Zhao, Runhan; Xiong, Chuang; Zhong, Weiyang; Luo, Xiaoji (Scientific reports, 2022)
The objective of this study was to evaluate the accuracy, reliability, and time requirements of two methods for measuring thoracolumbar kyphosis: a conventional method using a picture archiving and communication system (PACS) and this new method using the integrated inclinometer of a smartphone. The thoracolumbar kyphotic angles of one hundred consecutive patients were measured by a PACS and this novel smartphone method. The measured angles were analysed by multiple statistical methods, and the two measurement tools were compared in terms of accuracy, reliability, and time requirements. The mean result of thoracolumbar kyphosis measured by the PACS was 21.43 ± 12.96°, and the mean value measured by the smartphone was 21.03 ± 13.01°. A Bland–Altman plot for these two methods showed a mean difference of 0.4°, with the limits of agreement being -2.4° and 3.2°. One-way ANOVA showed no significant difference (F = 0.080, P = 0.999) among measurements by different observers and different methods. The intraclass correlation coefficients (ICCs) of the mean values of four repeated measurements of thoracolumbar kyphosis between these two methods were 0.997 (0.995–0.998), revealing that the two methods were highly correlated. The ICC results showed that the concordance between these two methods was very good for all measurements of thoracolumbar kyphosis, and the inter- and intra-observer reliability of the novel smartphone method were very good. The PACS method (36.95 ± 0.98 s) took significantly longer than the smartphone method (17.68 ± 0.97 s) when compared by an independent-samples t test ( P = 0.000). This new method using the integrated inclinometer of a smartphone has satisfactory validity and reliability compared to the PACS method. Additionally, the new method took significantly less time than the PACS method. Measuring with a smartphone is more convenient than using a PACS, which is always rooted in a full-sized computer. In summary, this new method using the integrated inclinometer of a smartphone is rapid, convenient, accurate and reliable when measuring thoracolumbar kyphosis in osteoporotic vertebral compression fracture (OVCF) patients.